2019
DOI: 10.3892/ijmm.2019.4255
|View full text |Cite
|
Sign up to set email alerts
|

CaSR activates PKCδ to induce cardiomyocyte apoptosis via ER stress‑associated apoptotic pathways during ischemia/reperfusion

Abstract: Endoplasmic reticulum (ER) stress can be activated by ischemia/reperfusion (I/R) injury in cardiomyocytes. Persistent ER stress, with an increase in intracellular ca 2+ ([ca 2+ ]i) concentration, leads to apoptosis. Protein kinase c (PKc) has a key role in myocardial damage by elevation of [ca 2+ ]i. The calcium-sensing receptor (caSR), a G protein-coupled receptor, can increase the release of [ca 2+ ]i from the ER through the inositol triphosphate receptor (IP 3 R). Intracellular calcium overload has been dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…This reduced expression of CaSR enhanced the vasodilation of the arteries and regulated the vascular tension and the blood pressure in the rats through the PLC-IP3/cAMP/RAAS pathways [27]. In rats with spontaneous hypertension, AngII also activates CaSR, as well as NLRP3 inflammasome in vSMCs [78].…”
Section: Hypertensionmentioning
confidence: 97%
“…This reduced expression of CaSR enhanced the vasodilation of the arteries and regulated the vascular tension and the blood pressure in the rats through the PLC-IP3/cAMP/RAAS pathways [27]. In rats with spontaneous hypertension, AngII also activates CaSR, as well as NLRP3 inflammasome in vSMCs [78].…”
Section: Hypertensionmentioning
confidence: 97%
“…The CaSR, a PLC sensitive G protein-coupled receptor, can increase the release of [Ca 2+ ]i from the endoplasmic reticulum via the inositol triphosphate receptor (IP3R). Notably, Liu et al demonstrated that CaSR activated PKCδ to induce cardiomyocyte apoptosis during ischemia/reperfusion (I/R) injury [44]. However, the associations between CaSR, PLC, PKCδ, and DMED are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of DRP1 in this process is illustrated by observations that, in the settings of DRP1 inhibition achieved by knockdown or overexpression of dominant negative mutant forms of the protein, DRP1 docking to the OMM is impaired and release of cytochrome c is prevented or delayed [114,122,123]. Finally, DRP1-mediated fission, and the interaction between DRP1 and Bax/Bak oligomers, also involves mitochondrial-ER contact sites along the OMM [66,69,124,125] (Figure 4), with ER stress and ER-mediated calcium release being sufficient to serve as stimuli for DRP1 recruitment and initiation of Bax/Bak oligomerization and MOMP [66,125]. Taken together, these observations underscore the concept that DRP1 (and DRP recruitment to mitochondria) is at the nexus of mitochondrial quality control, pathologic fission, and apoptotic cell death via the intrinsic pathway.…”
Section: Mitochondrial Outer Membrane Permeabilization: When Fission mentioning
confidence: 99%
“…For example, Bax/Bak-mediated MOMP has been shown to occur in response to transmission of ER stress to the mitochondria and subsequent sequestration of calcium within the mitochondrial matrix. These hallmarks of apoptosis (i.e., matrix swelling and calcium overload) are, in turn, accompanied by disruption of cristae architecture, loss of mitochondrial membrane potential and OPA1 degradation [66,124,163]. Moreover, putative triggers of MOMP, including Bax/Bak and DRP1, have been shown to regulate cristae morphology by induction of OMA1 and destabilization of OPA1 oligomers-a sequence of events that mobilize cytochrome c release from cristae [156,159].…”
Section: Disruption Of Cristae Architecture: Opening the Cytochrome Cmentioning
confidence: 99%